The Correlation of Watching English Movies Habit and Listening Skill - Pakaya, Mohamad Hendri; Saleh, Yuwin R; Ayuba, Hasan (Journal of English Language Teaching, Linguistics, and Literature Studies, 2024)
English movies are one of the most effective and enjoyable ways to develop listening skills. However, some students still find it difficult to understanding listening in teaching English. This research aims to determine whether there is a correlation between students’ habit in watching English movies and listening skill. The research method used quantitative correlational approaching involving 30 sixth semester students at English Education Department of IAIN Sultan Amai Gorontalo.  The data collection was done using a questionnaire about watching habit to English movies and a listening test. The data analysis was performed using Pearson Product Moment Formula. The result showed that there is a strong positive correlation between habit in watching English movies and listening skill of English Education Department sixth semester students (r = 0.667). This indicates that the more intense the students’ habit in watching English movies, the better their listening skill.Keywords:        Watching Habit, English Movies, Students’ Listening